Social Transformation of Ukraine Within the Framework of Economic Globalization - Merzlyak, Anzhela (Wydawnictwo Uniwersytetu Rzeszowskiego, 2007)
In the article there is stressed that development of Ukrainian economy requires binding close relationships with other countries as well as joining the process of international economic integration. The role of Poland is pointed out as a recipient country of direct Ukrainian investments.

W artykule podkreślono, że rozwój gospodarki Ukrainy wymaga nawiązania bliskich stosunków z innymi państwami, a także dołączenia do procesu międzynarodowej integracji ekonomicznej. Zauważa się rolę Polski jako adresata bezpośrednich inwestycji ukraińskich.
Społeczna transformacja Ukrainy w uwarunkowaniach globalizacji gospodarczej